2018
DOI: 10.2134/agronj2017.11.0678
|View full text |Cite
|
Sign up to set email alerts
|

Application Methods of Organic Poultry Feather Meal to Flue‐Cured Tobacco

Abstract: Optimal application methods of organic poultry feather meal for flue-cured tobacco (Nicotiana tabacum L.) production are unknown. Research was conducted in 2012 and 2013 to quantify the effects of two poultry feather meal sources, 13-0-0 Nature Safe and 12-1-0 Nutrimax, applied using three different methods: 100% broadcast before transplanting, 50% broadcast before transplanting + 50% sidedress, 10 d after transplanting, and 100% sidedress 10 d after transplanting. A conventional N treatment comprised of 28% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As documented in other organic tobacco production research, there is considerable risk of late ripening and maturation in the tobacco product in low moisture environments (Bennett et al, 2018). While the use of a cover crop does not ameliorate this concern, in the comparison of a typical N regimes under organic N management to cover crop alternatives, this study found evidence indicating the capacity for incorporation of cover cropping into flue-cured tobacco systems without compromising the quality of the cured leaf.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…As documented in other organic tobacco production research, there is considerable risk of late ripening and maturation in the tobacco product in low moisture environments (Bennett et al, 2018). While the use of a cover crop does not ameliorate this concern, in the comparison of a typical N regimes under organic N management to cover crop alternatives, this study found evidence indicating the capacity for incorporation of cover cropping into flue-cured tobacco systems without compromising the quality of the cured leaf.…”
Section: Discussionmentioning
confidence: 44%
“…Conventional practices were utilized to examine a specific organic management practice: the incorporation of leguminous cover crops. Other studies have used similar methodology to explore questions where measurements of completely organic production were not the goal Bennett et al, 2018).…”
Section: Field Management Nutrient Sources and Application Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, pen_based compost (FC) is not applied or produced; however, research notes that feather-based compost is a bio-bone with excellent characteristics for its high content of organic matter and nitrogen (Florida and Reategui, 2019) and that it shows great potential to be used in agriculture (Florida, 2019), particularly in crops that require low but constant amounts of nitrogen, as evidenced in organic tobacco (Bennett et al, 2018;Vann et al, 2017) and cocoa that responds negatively to excess fertilization (Puentes et al, 2014) could show positive results regarding the application of this bio-fertilize.…”
Section: Introductionmentioning
confidence: 99%